URGENSI KURSUS CALON PENGANTIN DI KUA KECAMATAN PARE KABUPATEN KEDIRI - Mohammad Hendy Musthofa (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2022)
The execution of the prospective bride and groom course is a move by the government, in this case the Director General of Islamic Guidance under the Ministry of Religion with the executor of the Office of Religious Affairs (KUA), to offer a provision for the prospective bride and groom who will carry out the marriage in the form of guidance and counsel so that later the bride and groom may have a happy and prosperous family life after carrying out the marriage. For this kind of research, qualitative approaches are used, which entail interviewing people and objects of the study and then gathering their data by direct observation. According to the study's findings, the prospective bride and groom course has been put into practice in the KUA Pare District. The prospective bride and groom course ran into a number of challenges during execution, the first of which was a lack of funding and time. The execution of the prospective bride and groom course is crucial to carry out given the current circumstances, where the divorce rate is rising. So that the soon-to-be bride and groom have the necessary information, including an understanding of their respective duties and rights, and are capable of resolving issues that arise in the home, in order to form a long-lasting and happy family and have a positive influence on the government by lowering the divorce rate.